Hubungan Antara Gaya Kepemimpinan Demokratis Dengan Motivasi Berprestasi Pada Anggota UKM X Universitas X - Muhammad Syahrul; Pratiwi Sakti (JURNAL PSIMAWA, 2021)
Democratic Leadership Style is the ability to influence others to want to work together to achieve the goals that have been set by means of various activities to be carried out jointly determined by the leader and its members and open equal opportunities for its members to participate more actively so that it can generate motivation to achieve an achievement. both for the organization and for themselves. This research is conducted on members of UKM X in University X by using correlational quantitative research methods. Purposive Non-Random Sampling is used in technique . The research sample amounted to 62 persons. The research data are obtained using the democratic leadership style scale instrument based on the Lippits & White theory and the achievement motivation scale based on the MC Clelland theory. The research tets is conducted by using correlation test. The results indicates that there is a relationship between democratic leadership style and achievement motivation with a correlation value of r = 0.587; p= 0.000 (p <0.005) which indicates that there is a significant relationship between democratic leadership style and achievement motivation. This shows that the higher the democratic leadership style, the higher the achievement motivation.